Association between referral source and duration of untreated psychosis in pathways to care among first episode psychosis patients in Northern Malawi. Issue 5 (27th October 2019) - Kaminga, Atipatsa C.; Myaba, Japhet; Dai, Wenjie; Liu, Aizhong; Chilale, Harris K.; Kubwalo, Paul F.; Madula, Precious; Banda, Richard; Pan, Xiongfeng; Wen, Shi W.
Abstract: Aims: To examine the association between referral source and duration of untreated psychosis (DUP) and explore determinants of referral source; when adjusting for pathways to care, positive and negative symptoms, diagnosis and socio‐demographic characteristics. Methods: A total of 140 subjects with first episode psychosis (FEP) were enrolled from a pilot early intervention service for psychosis in Northern Malawi between June 2009 and September 2012. Logistic regression analyses were used to quantify the associations between variables of interest. Results: Age ranged between 18 and 65 at assessment, with median, 33. Median DUP was 12.5 months. First contact did not independently determine DUP. Long DUP (>6 months) was associated with referral from community based volunteer (CBV) or traditional healer (TH), a unit increase in severity of negative symptoms and having schizophrenia, which was also associated with referral from CBV or TH. Additionally, being unemployed was associated with referral from CBV or TH. However, a unit increase in the number of times religious advice (RA) was sought, GP was contacted and severity of positive symptoms was associated with referral by GP. Conclusions: Mental health awareness is justified for this population and collaboration with THs in identifying and treating patients with psychosis may help reduce treatment delays. Access to mental health services ought to improve, particularly for the unemployed group. Future studies should consider adjusting for referral source when ascertaining first contact source as a predictor of DUP.